Bis-silylation of internal alkynes enabled by Ni(0) catalysis - Yun Zhang (Nature Portfolio, 2021)
Bis-silylated alkenes offer the advantage of two functional handles with distinguished reactivity for downstream functionalization. Here, the authors report a nickel-catalyzed bis-silylation of internal alkynes to versatile silylated alkene intermediates which can be chemoselectively manipulated.